Middleware Component Using Enterprise Java Bean (EJB) - Kannan, Kavitha (2003)
Component-based software development promises to decrease software development and maintenance costs and also providing sophisticated facilities for software reuse. A component is a chunk of software that provides functionality such as login validation, customer transaction and calculation [3]. It is encapsulated which means, that it can only be accessed via its interface and can be combined with other systems [3]. Most of these characteristics are derived from object oriented development. Therefore this paper presents an overview and development of component based software using J2EE framework called Enterprise Java Bean (EJB). The aim of this proj ect is at capturing the middleware concept using EJB where this architecture provides loose coupling of presentation layer and business logic. Moreover, leads Having two different clients connecting to a single middleware component which resides in the container of J2EE Server. The details about design and development of this middleware component and testing this component on to a test bed called bookstore application is the heart of this project. This paper will also introduce about the advantage of EJB against distributed component model and the interoperability of this middleware component across different platform and programming languages.